Synthesis of Acrylic Acid/Polyurethane Hybrid Emulsions and Characterization on the Properties for Acrylic Acid/Polyurethane Films - Chen, Guangmei; Yang, Mingdi; Xuan, Han (Asian Journal of Chemistry, 2012)
The acrylic acid/polyurethane (PUA) hybrid emulsion was prepared by water-borne polyurethane (WPU) modified with acrylic acid. The morphology of acrylic acid/polyurethane latex was characterized by FTIR, TEM and a light scattering method. The results displayed that the size of core-shell particles was between 60-120 nm. The result of FTIR indicated that the hydrogen bonding interaction in water-borne polyurethane changed with the addition of acrylic acid. The results of DSC indicated that the phase separation existed obviously in acrylic acid/ polyurethane when acrylic acid reached 75 wt %. With the increasing of acrylic acid in the hybrid emulsions, the thermal stability, mechanical properties and water resistance of acrylic acid/polyurethane were improved.